Pandemic H1N1 influenza A viruses suppress immunogenic RIPK3-driven dendritic cell death - Boris M. Hartmann (Nature Portfolio, 2017)
The differences in virus-host interactions resulting in distinct pathogenicity of seasonal and pandemic influenza A viruses (IAV) are not well understood. Here, the authors show that the hemagglutinin segment from pandemic, but not seasonal, IAV suppresses RIPK3-mediated dendritic cell death, thereby reducing T cell activation.